Synthesis and profiling of a 3-aminopyridin-2-one-based kinase targeted fragment library: Identification of 3-amino-5-(pyridin-4-yl)pyridin-2(1H)-one scaffold for monopolar spindle 1 (MPS1) and Aurora kinases inhibition. Issue 11 (15th July 2018) - Fearon, Daren; Westwood, Isaac M.; van Montfort, Rob L.M.; Bayliss, Richard; Jones, Keith; Bavetsias, Vassilios
Graphical abstract: Synthesis, biological evaluation, and structural studies of a kinase targeted 3-aminopyridin-2-one-based library identified ligand efficient inhibitors of MPS1 and Aurora kinases. Abstract: Screening a 3-aminopyridin-2-one based fragment library against a 26-kinase panel representative of the human kinome identified 3-amino-5-(1-methyl- 1H -pyrazol-4-yl)pyridin-2( 1H )-one (2 ) and 3-amino-5-(pyridin-4-yl)pyridin-2( 1H )-one (3 ) as ligand efficient inhibitors of the mitotic kinase Monopolar Spindle 1 (MPS1) and the Aurora kinase family. These kinases are well recognised as attractive targets for therapeutic intervention for treating cancer. Elucidation of the binding mode of these fragments and their analogues has been carried out by X-ray crystallography. Structural studies have identified key interactions with a conserved lysine residue and have highlighted potential regions of MPS1 which could be targeted to improve activity and selectivity.